KARAKTERISTIK WIRAUSAHA DAN KETERAMPILAN KEWIRAUSAHAAN PADA PENGRAJIN NOKEN DI PAPUA BARAT DAYA - Athirah, Aldila Mawanti (Jurusan Sosial Ekonomi Pertanian Fakultas Pertanian Universitas Mataram, 2023)
Noken is one of the typical Papuan woven or knitted crafts that comes from wood fibers, leaves, and plant stems. This handicraft business is widely found in the Land of Papua as an ancestral cultural heritage and includes creative economy businesses. Activities in the form of utilizing individual creativity, skills and talents to create welfare and jobs that produce and utilize the creativity and inventiveness of individual craftsmen. These noken craftsmen are generally from women called Papuan mothers. Noken has values, meanings, and functions inherent in Papuan culture. However, in this modern era, it is increasingly challenging with the existence of fast-paced craft products by making noken from yarn. So that the essence of noken is different from when using noken made from plants. The availability of artisan human resources who have entrepreneurial characteristics and strong entrepreneurial skills is expected to make noken crafts continue to exist and become a productive and profitable business. The need for entrepreneurial characteristics and better entrepreneurial skills of noken artisans has been identified as an important element for Papuan noken artisans. The purpose of this study is to analyze the characteristics of entrepreneurship and entrepreneurial skills as well as their relationship with noken artisans in Southwest Papua. The research was carried out in Sorong-Southwest Papua Regency. The selection of the location was carried out deliberately (purposive) with the consideration that the location is one of the areas that is the center of noken craftsmen. The sample collection methods are snowball and quota sampling. The instrument used was a questionnaire. The analysis tools used descriptive. The data and information obtained will then be processed for qualitative and quantitative analysis. Qualitative analysis is carried out with descriptive non-parametric analysis, this analysis is packaged in the concept of self-presentation as an interpretation tool.